Controlling chain flexibility in collagen networks to produce hydrogels with distinct properties. Issue 2 (3rd April 2017) - Lian, Jiaxin; Mansel, Bradley W.; Ingham, Bridget; Prabakar, Sujay; Williams, Martin A. K.
ABSTRACT: The structure, mechanical properties, and optical density of gels prepared from collagen in a manner that induces the dynamical arrest of the constituent polymers before substantial fibrillogenesis can take place have been investigated. Small angle X-ray scattering and confocal laser scanning fluorescence microscopy reveal that these gels exhibit substantially different network structures, over length scales ranging from a few nanometers to many microns, when compared with traditional collagen networks in which fibrillogenesis is intentionally induced. The highly associated arrangements of the more flexible structural components found in the arrested network yield a considerably lower optical density and higher viscoelastic storage modulus when compared to a "conventional" collagen gel; while the small amount of fibrils that do manage to form still yield strain stiffening and account for the fact that at high strains, moduli from both systems fall onto the same master curve.